A zonal optimization solution to reliability security constraint unit commitment with wind uncertainty. (April 2022) - Malekshah, Soheil; Banihashemi, Farzad; Daryabad, Habib; Yavarishad, Niloufar; Cuzner, Robert
Abstract: In restructured power systems, Independent System Operator manages and handles the Reliability-Security Constraint Unit Commitment problems including reliability and security issues. In this paper, a novel two-level optimization approach is proposed to achieve reliable, secure, and optimal generation units' schedule while wind generation units are presents, in which the power system is divided to a number of zones. Uncertainties and time-dependent sources such as wind generation units are the most significant reasons for reliability challenges. In the proposed approach, load forecast and wind generation units' uncertainty have been considered. An intelligent search technique is implemented for reliability study. The proposed method is evaluated by simulation of the 6-bus, 118-bus, and 4672-bus test systems. The two-level optimization is compared to robust optimization and centralized methods. The results show the effectiveness and significance of this method.